2018
DOI: 10.1142/s0219519418400067
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Sensory Electrical Stimulation for the Suppression of Parkinsonian Rest Tremor

Abstract: This paper aims to investigate the effect of continuous sensory electrical stimulation (SES) on the suppression of a Parkinsonian rest tremor. Fourteen patients with Parkinson’s disease participated in this study. Three wrist muscles were electrically stimulated on sensory level under motor threshold. Intensity of stimulation was determined for each muscle of each patient as the maximum tolerable current amplitude that does not induce muscle contraction. Tri-axial gyro sensors were attached to three upper limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Among the review articles, ten studies reported the effects of peripheral electrical stimulation results on patients with ET [18][19][20][21][22][23][24][25][26][27] while ten studies reported on patients with PD [28][29][30][31][32][33][34][35][36][37] and seven studies included both patients with ET and patients with PD [16,17,[38][39][40][41][42]. In order to compare electrical stimulation strategies, some studies also included healthy volunteers that either mimicked tremorgenic activity during experimentation or were subject to artificially induced tremors for experimentation [31,38,41].…”
Section: Target Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the review articles, ten studies reported the effects of peripheral electrical stimulation results on patients with ET [18][19][20][21][22][23][24][25][26][27] while ten studies reported on patients with PD [28][29][30][31][32][33][34][35][36][37] and seven studies included both patients with ET and patients with PD [16,17,[38][39][40][41][42]. In order to compare electrical stimulation strategies, some studies also included healthy volunteers that either mimicked tremorgenic activity during experimentation or were subject to artificially induced tremors for experimentation [31,38,41].…”
Section: Target Populationsmentioning
confidence: 99%
“…However, the activation of afferent pathways with the real physiological tremorgenic phase is not achieved. Some studies applied electrical stimulation without following any time pattern or synchronization to mechanical or physiological events [21,22,28,[30][31][32][33][34][35]. This stimulation strategy has been labelled as continuous stimulation in this review (Fig.…”
Section: Stimulation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…2,7 Sensory electrical stimulation (SES) was shown to be effective at suppressing essential tremors 8,9 and Parkinson's disease resting tremors. 10 As artificial sensory signals, such as imposed passive movement, could modulate tremors in PD, 11 applying proper electrical sensory stimulation may be able to suppress tremors in PD patients. In contrast, no evidence of tremor modulation via sensory signals in SWEDDs patients has been noted.…”
Section: Introductionmentioning
confidence: 99%